Exploring the factors influencing innovative teaching practices in Moroccan primary schools: an exploratory study - Lkamel, Karim; Assermouh, Jalal (International Journal of Evaluation and Research in Education (IJERE), 2025)
In education, pedagogical innovation is crucial for improving student learning outcomes, but teachers’ adoption of innovative practices is influenced by various sociodemographic factors, which remain underexplored. This study aims to investigate how factors such as age, gender, education level, and prior training shape teachers’ engagement with innovative teaching methods. A quantitative analysis of 110 teachers from multiple schools was conducted, utilizing multiple correspondence analysis (MCA) to identify distinct teacher profiles based on their innovation practices. The findings revealed four key profiles: non-innovative teachers, who rely on traditional methods; active teachers, who adopt active learning strategies; untrained teachers, who work without formal training; and innovative teachers, who integrate information and communication technologies (ICT) and blended learning techniques. The study concludes that sociodemographic factors significantly impact the adoption of pedagogical innovation. To address this, targeted professional development and tailored policies are needed to support teachers in overcoming barriers and adopting innovative practices. By promoting a more inclusive and adaptive approach to teacher training, this research offers valuable insights to improve teaching effectiveness and ultimately enhance student engagement and learning outcomes.